Implementing Second-Generation Road Funds - Ajay Kumar (2012)
The note describes the response taken to the deteriorating condition of the road network and high associated economic cost, involving various stakeholder consultations held in the 1980s under the umbrella of the Bank-managed and donor-financed Road Maintenance Initiative (RMI), which set the broad outlines of a new policy framework for the road sector. The RMI has, since 1988, undertaken to develop awareness about the importance of road maintenance and has supported country level programs designed to identify the root cause of the problem and to initiate actions needed to set the management and financing of roads on a sustainable basis.